Navigating English Learning Challenges During the Pandemic: Insights from the National Learning Camp and Subsequent Performance Trends - Sosmeńa, Lizel (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to investigate the correlation between students' performance in English 8, the challenges they faced in learning English during the pandemic, and their performance after the National Learning Camp. The researcher utilized descriptive-correlational and comparative designs and employed the systematic sampling technique in identifying the 240 respondents from the Grades 9 learners of Dumaguete City National High School. The researcher used validated questionnaires and employed percentage, weighted mean, and multiple regression analysis in treating the data. The study revealed that the National Learning Camp (NLC) has shown a positive impact on the students' performance in English 8. The students' performance improved after the NLC, with a statistically significant difference. Additionally, the data revealed that the challenges faced by students in terms of access, equity, quality, resiliency, and well-being are moderate. There is a significant relationship between the extent of students' challenges in learning English during the pandemic in terms of access, suggesting that these issues may have influenced their performance.